An artificial inoculation protocol for Uromycladium acaciae, cause of a serious disease of Acacia mearnsii in southern Africa. Issue 1 (2nd January 2019) - Fraser, Stuart; McTaggart, Alistair R; Chan, Julian Moreno; Nxumalo, Thobile; Shuey, Louise S; Wingfield, Michael J; Roux, Jolanda
Abstract : Uromycladium acaciae is the cause of a severe wattle rust epidemic in plantations of Acacia mearnsii (black wattle) in southern Africa. Research on the biology of this damaging rust is assisting in the development of control strategies. One strategy under investigation is the identification and deployment of resistant lines of A. mearnsii . Selection of resistant families currently relies on large-scale, time-consuming and expensive field trials. In this study, we present a detailed artificial inoculation protocol for U. acaciae, which can be used to screen for resistance. The results of an experiment that used the protocol to screen the relative resistance of 12 families of A. mearnsii to U. acaciae are also presented. The developed artificial inoculation protocol can also be used to investigate several other aspects of this host–pathogen system.